Harnessing Artificial Intelligence for English Language Learning: A Systematic Literature Review - Batubara, Muhammad Hasyimsyah (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2025)
Integrating AI in education has transformed English language learning by offering personalized, adaptive, and interactive learning experiences. However, challenges such as technological accessibility, pedagogical integration, and maintaining human-centered learning approaches remain underexplored. This study aims to systematically review recent research on the use of AI-based adaptive platforms in ELL, focusing on their utilization, effectiveness, and overall impact. Employing the Systematic Literature Review method, 13 relevant studies published between 2020 and 2024 were analyzed using a structured protocol involving keyword identification, database selection, and strict inclusion-exclusion criteria. The findings reveal that AI technologies, such as chatbots, mobile applications, adaptive learning platforms, and virtual tutors, have significantly enhanced learners' language skills, engagement, motivation, and confidence. Challenges such as over-reliance on AI, critical thinking development, and digital inequalities were noted despite the benefits. The study implies that for AI to sustainably and effectively support ELL, balanced integration with human instruction, adequate technological infrastructure, and teacher training are essential. These insights offer valuable guidance for educators, policymakers, and technology developers in designing more inclusive, adaptive, and human-centered AI solutions for English education.